Exploring the surface of the Moon and Mars: What kind of ground vehicles are required?. (January 2019) - Baratta, M.; Genta, G.; Laurenzano, D.; Misul, D.
Abstract: On the surface of the Moon and Mars, the astronauts must have at their disposal means for exploring a suitable area of the planet. A ground vehicle was tested for the first time outside Earth during the Apollo program, but the longer stay and the wider extent of the exploration will make similar vehicles designed for Mars larger, faster and more complex. In later missions, transportation on the planet will possibly require aerial vehicles and finally the realization of a whole transportation infrastructure. Furthermore, robotic rovers will be required to assist the astronauts in their exploration duties. Highlights: Rovers are an essential asset for of Human exploration missions. Rovers for the astronauts require higher performance than those of robotic rovers. Rovers are often assumed to be very different from usual off-road vehicles. An electric driveline, powered by batteries or by fuel cells, is usually postulated. Current offroad automotive technology is suitable for planetary exploration rovers.